Reconstructing Landscape to Reconstruct Regionalism? L’Horta, la Ciutat de les Ciències, and the Ideological Politics of Valencian Modernity - Prytherch, David L. (Treballs de la Societat Catalana de Geografia, 2008)
In this paper I explore the ways economic and political reterritorialization such as regionalist politics in Spain may be negotiated through cultural discourses and landscapes. Few regions exemplify the contradictions of regional politics better than the Comunitat Valenciana, whose capital Valencia has been transformed by the Generalitat Valencianas simultaneous pursuit of economic development and political autonomy over two decades and three political administrations. Some of these changes imply the displacement of LHorta de Valencia, long a regional symbol, by new monumental spaces like the Ciutat de les Arts i de les Ciències. I examine this precipitous substitution of landscapes, in regional space and iconography, to analyze how the Generalitats reconstruction of the Valencian landscape may serve to reconstruct Valencian regionalism. In this essay, based on a broader qualitative research project, I suggest that a new regionalist discourse has emerged premised on global competitiveness and obsessed with modernity. Like the Museu de les Ciències itself, however, this new Valencian regionalism may be built for global tourism yet lacking substantial content.